Biliary dyskinesia - Sobol, Elżbieta; Muszyński, Jacek (Przewodnik Lekarza/Guide for GPs, 2005)
Biliary dyskinesia is defined as the motor disorders biliary ducts. This term embraces gallbladder dyskinesia and sphincter of Oddi dysfunction. The main symptoms of those abnormalities are episodes of severe pain in the epigastrium and right upper abdominal quadrant. The etiology of dyskinesia remain indistinct – it is considered that dyskinesia can be caused, among others, by: inflammations, muscles or nervous disorders, diabetes and hyperlipidemia, obesity, pregnancy, drugs effect. Diagnosing of dyskinesias is difficult. It takes to do a complicated investigation. Gallbladder dysfunction is suspected when gallbladder ejection fraction has an abnormal value (GBEF less than 40%) estimating during cholecystokinin infusion scintigraphy. If the GBEF is low, cholecystectomy is recommended. ”The gold standard” for determining sphincter of Oddi dysfunction is endoscopic manometry. The method of choice for SOD is endoscopic sphincterotomy.